CHI '06 Extended Abstracts on Human Factors in Computing Systems 2006
DOI: 10.1145/1125451.1125780
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge sharing, maintenance, and use in online support communities

Abstract: All rights reserved 2007ii For Maren iii ACKNOWLEDGEMENTSI am deeply appreciative of the many individuals who have helped shape this dissertation and continually encouraged me throughout its writing. I hope that each of them feels some sense of shared ownership of this work and is pleased to be associated with it. Although I can't mention everyone by name, a few are worth special notice.I owe much to my advisor Paul Resnick, who has played an instrumental role in my education since the day I showed up at SI. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 91 publications
(214 reference statements)
0
11
0
Order By: Relevance
“…As threaded conversations become embedded within more complex social spaces with multiple interaction technologies, it is increasingly important to understand how they all interact. For example, Hansen found that technical and patient support groups benefit from combining a threaded conversation (i.e., email list) with a more permanent wiki repository [12]. The Ravelry example showed strategies that have not yet been widely used by the research community to understand how network position relates to use of other tools (i.e., blogs) or activities (i.e., projects).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As threaded conversations become embedded within more complex social spaces with multiple interaction technologies, it is increasingly important to understand how they all interact. For example, Hansen found that technical and patient support groups benefit from combining a threaded conversation (i.e., email list) with a more permanent wiki repository [12]. The Ravelry example showed strategies that have not yet been widely used by the research community to understand how network position relates to use of other tools (i.e., blogs) or activities (i.e., projects).…”
Section: Discussionmentioning
confidence: 99%
“…There are a handful of administrators who keep the conversation friendly and encourage contributors to follow the guidelines. See [12] for a complete description of the community and some of the strategies they use that make them so effective.…”
Section: Analyzing a Technical Support Email List: Ccs-dmentioning
confidence: 99%
“…Participation is highly skewed: a small percentage of experts typically answer the majority of questions that are posed by a large number of novices (e.g., [11,12]). To help limit repeat questions, most help-based communities encourage newcomers to check discussion archives, FAQs, or community repositories before posting questions [9,11,12,14].…”
Section: Related Workmentioning
confidence: 99%
“…These can be used to provide personalized recommendations through the use of recommender systems (e.g., [17]). Alternately, visualization techniques can be used to provide context around conversations [9,18]. This can be useful in helping newcomers locate relevant messages and understand some of the social context around a message (e.g., it is sent from a frequent poster and is the 4th of 16 messages in the thread).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation